THE DEVELOPMENT OF ENRICHEMENT BOOK ON CONGRUENCE AND SIMILARITY COMBINED WITH GEOGEBRA FOR JUNIOR HIGH SCHOOL STUDENTS - Ramadhani, Rahma
Geometry is one of the mathematics content standards that students need to learn. Geometry is closely related to visualization. Particularly, congruence and similarity triangles and its application require accurate visualization so that students can better understand the meaning of congruent and similar. In this modern era, this can be resolved by using the help of an application, one of which is GeoGebra. The available features on GeoGebra can be used to demonstrate the applicability of the criteria for congruent and similar triangles so that students can deepen their understanding of the materials and actively construct their knowledge. Enrichment books also have a role in supporting learning that can complement the deepening of materials that is not fully presented in textbooks and enrich students' knowledge. With the hope that enrichment books can further explore students' knowledge of certain materials, this project aims to develop an enrichment book combined with GeoGebra that can support the deepening of understanding of congruence and similarity materials for junior high school students. The enrichment book is developed by adapting the ADDIE model which consists of Analyze, Design, Development, Implementation, and Evaluation. At the analysis stage, material analysis was carried out by reviewing the curriculum that was being applied at the time of the book development process, and the needs of book development was analyzed by reviewing the availability of learning resources. At the design stage, various references relevant to the material were collected and an outline of the enrichment book content was made. At the development stage, an enrichment book was produced which was then assessed by mathematics material experts and design experts to determine the feasibility of the book. The material experts assessed the material and representation aspects. Meanwhile, the design experts assessed the cover design and page/content design aspects. Both from the material aspect, presentation aspect, and design aspect, overall can be concluded that the enrichment book was suitable for use. In order to produce an enrichment book with better quality, at the development stage, book improvements were also made based on suggestions from material validators and design validators. In the implementation stage, the enrichment book that has been developed is tested on grade IX students who have studied congruence and similarity. At the evaluation stage, an analysis was carried out to determine the usefulness of the enrichment book by testing the difference in pre-test and post-test averages. Because the data of pre-test, post-test, and the difference are normally distributed, the t-test was conducted using paired t-test. With a significance level of 5%, there was enough evidence to conclude that the mean of the post-test was greater than the mean of the pre-test. Thus, the developed enrichment book has benefits for junior high school students in improving their understanding of congruence and similarity.